Cognitive response to testosterone replacement added to intensive lifestyle intervention in older men with obesity and hypogonadism: prespecified secondary analyses of a randomized clinical trial. Issue 5 (10th August 2021) - Gregori, Giulia; Celli, Alessandra; Barnouin, Yoann; Paudyal, Arjun; Armamento-Villareal, Reina; Napoli, Nicola; Qualls, Clifford; Villareal, Dennis T
ABSTRACT: Background: Both obesity and hypogonadism are common in older men which could additively exacerbate age-related declines in cognitive function. However, little is known about the effects of lifestyle intervention plus testosterone replacement therapy in this population. Objectives: In this secondary analysis of the LITROS (Lifestyle Intervention and Testosterone Replacement in Obese Seniors) trial, we examined whether testosterone replacement therapy would improve cognitive function when added to intensive lifestyle intervention in older men with obesity and hypogonadism. Methods: Eighty-three older, obese hypogonadal men with frailty were randomly assigned to lifestyle therapy (weight management and exercise training) plus testosterone (LT + Test) or lifestyle therapy plus placebo (LT + Pbo) for 6 mo. For this report, the primary outcome was change in the global cognition composite z score. Secondary outcomes included changes in z score subcomponents: attention/information processing, memory, executive function, and language. Changes between groups were analyzed using mixed-model repeated-measures ANCOVAs following the intention-to-treat principle. Results: Global cognition z score increased more in the LT + Test than in the LT + Pbo group (mean change: 0.49 compared with 0.21; between-group difference: −0.28; 95% CI: −0.45, −0.11; Cohen's d = 0.74). Moreover, attention/information z score and memory z score increased more in the LT + Test than in the LT + Pbo group (mean change: 0.55 compared with 0.23; between-group difference: −0.32; 95% CI: −0.55, −0.09; Cohen's d = 0.49 and mean change: 0.90 compared with 0.37; between-group difference: −0.53; 95% CI: −0.93, −0.13; Cohen's d = 1.43, respectively). Multiple regression analyses showed that changes in peak oxygen consumption, strength, total testosterone, and luteinizing hormone were independent predictors of the improvement in global cognition ( R 2 = 0.38; P < 0.001). Conclusions: These findings suggest that in the high-risk population of older men with obesity and hypogonadism, testosterone replacement may improve cognitive function with lifestyle behaviors controlled via lifestyle intervention therapy. This trial was registered at clinicaltrials.gov as NCT02367105.